Listening and learning: the need for a compassionate and patient-centered approach for longstanding AN - Jennifer L. Gaudiani (Journal of Eating Disorders)
Abstract A 2022 paper proposing preliminary clinical characteristics of adults with anorexia nervosa who might be supported in compassionate end-of-life care generated public dissent in the peer-reviewed literature and the media as well as private expressions of support. Several years of listening and learning by the lead author resulted in a greater understanding of personal, clinical, and scholarly concerns that arose as a result of this article. In this piece, the lead author expressly disavows the concept and phrase of “terminal anorexia nervosa.” This essay attempts to acknowledge the original article’s inadequacies, aims to bring clarity and specificity to the issue, and calls for ongoing discussions and collaboration to improve treatment for our complex and vulnerable patients.